2002
DOI: 10.1063/1.1454995
|View full text |Cite
|
Sign up to set email alerts
|

The role of sound propagation in concentrated colloidal suspensions

Abstract: In a suspension, the hydrodynamic interactions between particles can propagate by two mechanisms: relatively slowly, by the diffusion of transverse momentum, or relatively rapidly, by the propagation of sound waves. Here we describe computer simulation results for the collective and single particle dynamics of colloidal particles with the aim of clarifying the role of sound. We find that for single particle motion the effect is rather trivial. As for an isolated particle, compressibility modifies the decay of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…The squareroot singularity in Eq. In simulations, however, the discontinuity is not observed due to the finite compressibility of the fluid [24,4,6]. In a compressible solvent, the sound propagation occurs with a finite speed, and the solvent surrounding the colloid is not instantly set in motion.…”
Section: Velocity Autocorrelation Functionmentioning
confidence: 95%
“…The squareroot singularity in Eq. In simulations, however, the discontinuity is not observed due to the finite compressibility of the fluid [24,4,6]. In a compressible solvent, the sound propagation occurs with a finite speed, and the solvent surrounding the colloid is not instantly set in motion.…”
Section: Velocity Autocorrelation Functionmentioning
confidence: 95%
“…ref. [89]. Because t cs ≪ τ ν , the sound-wave contribution to the VACF decays much faster than the hydrodynamic contribution V (t)V (0) H or even than the Langevin approximation V (t)V (0) L (recall that τ ν = 9 2 τ B for neutrally buoyant colloids.)…”
Section: Vacf At Long Timesmentioning
confidence: 98%
“…For that reason, sound effects are often ignored for colloidal suspensions under the assumption that they will have dissipated so quickly that they have no noticeably influence on the dynamics. However, some experiments [88] and theory [89] do find effects from sound waves on colloidal hydrodynamics, so that this issue is not completely settled yet. The kinematic time, τ ν , defined in Eq.…”
Section: Hydrodynamic Time-scales For Colloidsmentioning
confidence: 99%
“…[15]. Computer simulations revealed that the origin of this phenomenon lies in multiple scattering of sound waves [16], implying that the role of sound effectively extends to times much longer than the sonic time. Such phenomena highlight the importance of a solid theoretical understanding of the interplay between the sonic and the viscous effects.…”
Section: Introductionmentioning
confidence: 99%